Linked Data Architecture for Plan Execution in Distributed CPS - Berezovskyi, Andrii; El-khoury, Jad; Fersman, Elena (IEEE International Conference on Industrial Technology (Online), 2019)
Future cyber-physical systems (CPS) require their components to perform autonomously. To do that safely and efficiently, CPS components will need access to the global state of the whole CPS. These components will require near real-time updates to a subset of the global state to react to changes in the environment. A particular challenge is to monitor state updates from the distributed CPS components: one needs to ensure that only states consistent with the PDDL plan execution semantics can be observed within the system. In order to guarantee that, a component to monitor plan execution is proposed. Microservices based on Linked Data technologies are used to provide a uniform way to access component states, represented as Resource Description Framework (RDF) resources. To ensure the correct ordering of state updates, we present an extension of the OASIS OSLC TRS protocol. Specifically, we strengthen the ordering guarantees of state change events and introduce inlining of the state with the events to prevent state mismatch at the dereferencing stage.